Cytotoxic, Antiproliferative and Apoptotic Effects of New Benzimidazole Derivatives on A549 Lung Carcinoma and C6 Glioma Cell Lines - Yurttas, Leyla; Demirayak, Seref; Akalın Ciftci, Gulsen (Anti-Cancer Agents in Medicinal Chemistry, 2015)
Benzimidazole ring is a versatile structure which has been extensively utilized in medicinal chemistry. Since we are working on 1,2-disubstutited benzimidazoles, we have reported new antitumor active derivatives. As a continuation to our previous work, we have synthesized a new series of 1-(2-aryl-2-oxoethyl)-2-[(N,Ndimethylamino/ pyrrolidinyl/piperidinyl)thiocarbamoyl] benzimidazole derivatives. Anticancer activity of the compounds was evaluated using MTT assay, BrdU assay and flow cytometric analysis on A549 human lung carcinoma and C6 rat glioma cell lines. Compounds bearing dimethylamino moiety exhibited higher antitumor activity.
Keywords: benzimidazole